Dynamic evolution of amplitude and position of geomagnetic secular acceleration pulses since 2000 - Bai, Chunhua; Gao, Guoming; Wen, Limin; Kang, Guofa (Frontiers in Earth Science, 2024)
This study examines the behavior characteristics of geomagnetic secular acceleration (SA) pulses to enhance comprehension of the dynamic process of the Earth’s core. The analysis statistically evaluates the evolution of the SA pulse amplitude and position since 2000 by computing the three-year difference in SA with the CHAOS-7 geomagnetic field model (CHAOS-7.17 release). Furthermore, the study explores the correlation between the acceleration pulse amplitude and geomagnetic jerks and the dynamic processes of alternating variation and polarity reversal of pulse patches over time. Research findings indicate that the variation in pulse amplitude at the Core Mantle Boundary (CMB) closely resembles that observed at the Earth’s surface, with an average period of 3.2 years. The timing of peak pulse amplitude aligns with that of the geomagnetic jerk, suggesting its potential utility as a novel indicator for detecting geomagnetic jerk events. The acceleration pulses are the strongest near the equator (2 ºN) and more robust in the high-latitude region (68 ºS) of the Southern Hemisphere, indicating that the variation is more dramatic in the Southern Hemisphere. The acceleration pulses fluctuate unevenly in the west-east direction, with characteristics of local variation. In the Western Hemisphere, the pulse patches are distributed near the equator, exhibiting an evident westward drifting mode. The positive and negative patches alternate in time, displaying a polarity reversal in the west-east direction, with an average interval of approximately 32 º. These characteristics can be attributed to the rapid magnetic field fluctuations disclosed by the model of stratification at the top of the Earth’s core. In the Eastern Hemisphere, the pulses are weaker between 10 ºE and 60 ºE, with the most active pulses occurring around 80 ºE to 105 ºE and near 150 ºE. The pulse patches exhibit a broader distribution in the north-south direction, with relatively strong patches still occurring near 40 ºN and 40 ºS. These local variation characteristics match the actual cases of zonal flows and geostrophic Alfvén waves in the Earth’s core. These research results provide new clues for understanding the Earth’s core dynamic process of geomagnetic acceleration pulses.